A Dependency on Non-Timber Forest Products Utilization by the Jagoi Bidayuh in Bau District, Sarawak, Malaysia - Alfred, Keleman (UNIVERSITI MALAYSIA SARAWAK, 2024)
Non-timber forest products (NTFPs) are significant for the well-being of millions of individuals, particularly those living close to the forest and intently depend on them for day-to-day use. The study is aimed to determine the Jagoi community’s dependency on NTFPs with the specific objectives; (1.) Examine the pattern of NTFPs utilization according to purpose of utilization, location of collection, and frequency of collection, (2.) Relate the socio-economic factor(s) influencing the NTFPs utilization, and (3.) Access the perceptions of the local community on aspects of community dependency on the Jagoi Heritage Forest (JHF), socio-economic implications from the conservation plan, and management of the heritage forest. A total of 235 respondents from seven villages surrounding Jagoi Heritage Forest have been selected and involved in the survey. The result of the study showed that the Jagoi Bidayuh community depends on forest resources for living and the forest also provided them with ecosystem services. A Spearman correlation analysis then found five significant correlations with only one showing some slight positive relationship, which was between the frequency of firewood collection and age level. It showed that the older respondents are, the higher the frequency of firewood collection. The other four correlations have weak relationships. The community has expressed their thoughts on wanting to preserve the history and culture of the old village on top of Mount Jagoi. They were also committed to join forces with the Jagoi Area Development Committee (JADC) to develop and manage the forest, and they believe a proper management plan should be prepared to ensure all the conservation goals are achieved.